Risk management and policy imperatives: regulating buy now, pay later (BNPL) in Malaysia - Edward, Oswald Timothy; Hassan, Suzana (Universiti Teknologi MARA, Johor, 2025)
The rapid growth of Buy Now, Pay Later (BNPL) schemes has transformed consumer credit practices globally and in Malaysia. BNPL offers consumers short-term instalment financing, often without interest, and has become popular among younger, digitally savvy demographics. While BNPL promotes financial inclusion and retail expansion, it raises significant concerns regarding credit risk, household debt, consumer protection, regulatory oversight, and systemic financial stability. This paper reviews existing literature on BNPL adoption and risk management in Malaysia, situating it within regional experiences in Singapore, Indonesia, and Australia. Findings highlight five major risk domains: credit risk and household debt, consumer protection and financial literacy, regulatory and governance gaps, operational and cybersecurity vulnerabilities, and Environmental, Social, and Governance (ESG) considerations. The forthcoming Consumer Credit Act (CCA) in Malaysia is identified as a critical step toward addressing governance challenges, but gaps remain in empirical research, cross-platform indebtedness, and ESG integration. The review concludes that sustainable BNPL growth in Malaysia requires a multi-dimensional risk management framework balancing innovation with consumer protection and financial stability